KURIKULUM PENDIDIKAN AGAMA ISLAM DI SEKOLAH DASAR - Aslan Aslan (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
Content standards are the scope of material and competency levels to achieve graduate competence at certain levels and types of education, which are outlined in the graduation competency criteria, study material competencies, subject competencies and learning syllabus. Graduate competency standards are qualifications for graduate abilities that include knowledge, attitudes and skills. The curriculum is developed according to the educational unit, the potential and characteristics of the area as well as the socio-culture of the local community and students.